Shortcomings in the Workplace Whistleblower Protection in France: What to Expect from the Transposition of Directive 2019/1937? - Bargain, Gwenola (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
At first glance, the French legal framework for whistleblower protection may appear to be particularly well developed. Indeed, since the so-called Sapin II Law, it has offered general criteria to qualify a person as a whistleblower and set procedural and substantive guarantees against possible retaliatory measures. Although advanced, the system is not complete. Its shortcomings are repeatedly mentioned, to the extent that the transposition of European Directive (EU) 2019/1937 of 23 October 2019 is an opportunity to correct the limitations of the current system. No matter if the criteria may be too restrictive, the procedure too constraining or the protective measures insufficient, there are many elements that need to be modified. However, a question may arise as to whether a unitary treatment of the alert is possible when it does not always serve the same purpose.